RESPON KACANG HIJAU (Phaseolus radiatus L.) TERHADAP EKSTRAK REBUNG BAMBU BETUNG (Dendrocalamus asper Backer.) DENGAN PUPUK HIJAU TITHONIA (Tithonia diversifolia (Hemsley) A. Gray) - Aryanti, Deci; Adiwirman, Adiwirman; Tabrani, Gunawan (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The purpose of this study was to improve the productivity of mung beans bythe betung bamboo sprout extract with tithonia green compost. This study was carried out at the experimental station ofAgriculture Faculty, Riau University Pekanbaru from June to September 2016. The study was conducted in the completely randomized design (CRD) factorial experiment 3 x 3 in 3 replications. The first factor wasthe concentration of betung bamboo sprout extract: 0 ppm, 4,500 ppm and 6,000 ppm. The second factor was the doses of tithonia green compost:0 kg/2m2, 2,00 kg/2m2, and 4.00 kg/2m2. The variables those observed were plant height, primary branch numbers, flowerinitiation, the pods ripen age, period of harvest, pods per plant, pithy pods per plant, seed weight, seed dry weight, and weight of 100 seeds.The result suggestednumbers of mung beans primary branch increased, the flowering more accelerated, the pods harvestedwas a longer period if given of betung bamboo sprout extracts 6,000 ppm or the plant would be higher, the age pods to be mature, the pods harvest to be longer and weight of 100 seeds was weightier ifthe plants given tithoniagreen compost4,00 kg/2 m2. Keywords: Mung bean production, betung bamboo sprout extract, tithonia green compost